New insights on the interplays between m6A modifications and microRNA or lncRNA in gastrointestinal cancers - Su, Tao; Liu, Jiandong; Zhang, Nasha; Wang, Teng; Han, Linyu; Wang, Suzhen; Yang, Ming (Frontiers in Cell and Developmental Biology, 2023)
N6-Methyladenosine (m6A) methylation is one of the most extremely examined RNA modifications. M6A modification evidently impacts cancer development by effecting RNA metabolism. Long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) are involved in multiple essential biological processes by regulating gene expression at the transcriptional and post-transcriptional levels. Accumulated evidences indicated that m6A is involved in regulating the cleavage, stability, structure, transcription, and transport of lncRNAs or miRNAs. Additionally, ncRNAs also play significant roles in modulating m6A levels of malignant cells by participating in the regulation of m6A methyltransferases, the m6A demethylases and the m6A binding proteins. In this review, we systematically summarize the new insight on the interactions between m6A and lncRNAs or miRNAs, as well as their impacts on gastrointestinal cancer progression. Although there are still extensive studies on genome-wide screening of crucial lncRNAs or miRNAs involved in regulating m6A levels of mRNAs and disclosing differences on mechanisms of regulating m6A modification of lncRNAs, miRNAs or mRNAs in cancer cells, we believe that targeting m6A-related lncRNAs and miRNAs may provide novel options for gastrointestinal cancer treatments.